2022
DOI: 10.3390/genes13091532
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Klotho G395A and C1818T Polymorphisms and Their Association with Serum Glucose Level and Risk of Type 2 Diabetes Mellitus

Abstract: Objective: The objective was to study the association of Klotho gene G395A and C1818T single nucleotide polymorphisms with glycemia, serum, glycosylated hemoglobin (HbA1c) level and the risk of type 2 diabetes mellitus (T2DM) in the Pashtun population of Pakistan. Methods: In this study, 195 normal individuals and 217 T2DM patients were enrolled. All subjects were divided into three groups, namely overall subjects (control + T2DM patients), control individuals and T2DM patients, and their fasting glucose, HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…One prospective study of participants with primary hyperoxaluria type 1 found that those with KS had lower levels of Klotho than individuals without nephrocalcinosis and CaOx KS [ 27 ]. Klotho gene G395A single-nucleotide polymorphisms were linked to the formation of renal stones among North Indian patients with KS [ 28 ]. Moreover, a meta-analysis involving five distinct research studies revealed that Klotho prevented the development of urinary stones [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One prospective study of participants with primary hyperoxaluria type 1 found that those with KS had lower levels of Klotho than individuals without nephrocalcinosis and CaOx KS [ 27 ]. Klotho gene G395A single-nucleotide polymorphisms were linked to the formation of renal stones among North Indian patients with KS [ 28 ]. Moreover, a meta-analysis involving five distinct research studies revealed that Klotho prevented the development of urinary stones [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such diabetic and high oxidative stress conditions, studies have shown that pro-diabetic, pro inflammatory and pro-oxidative stress genes are highly expressed. Several studies have reported altered gene expressions in such conditions ( Shaik et al, 2010 ; Safi et al, 2018 ; Bima et al, 2022a ; Aziz et al, 2022 ; Bima et al, 2022b ). In a recent study, Hall et al reported a significant impact of high glucose exposure on global gene expression and DNA methylation in human pancreatic islets ( Hall et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to act as a co-receptor for FGF 23, which helps to regulate calcium and phosphorus metabolism 7 . Studies have shown that α-Klotho inhibits insulin signaling 9 , regulates glucose and fat metabolism 10 and plays a role in the central regulation of energy balance 11 . Recent studies have shown that diabetic patients have reduced serum Klotho levels 12 14 .…”
Section: Introductionmentioning
confidence: 99%